IOT Based Energy Meter Reading System with Automatic Billing - C. Kishore Kumar, P; Antony Veera Puthira Raja, J; Ebenezer Abishek, B; Vishalakshi, S; Vidhya, G (International Journal of Engineering and Technology, 2018)
In recent time e-meter (electronic meter) place a major role for the power consumption &cost efficient system. In advanced future it has high reliable and productive programmed meter perusing framework (AMRS). This paper aims to plan a straightforward ease.IOTbased energy meter reading system which includes fault indication. Unit usage after (i.e. for 15 days once). Mode selection (automatic& manual) and SMS alert to user. Mode selection option is included. To avoid more power consumption automatic mode is used to cut-down the appliances for the user convenience. If there is a fault in the e-meter it sends a notification to the user. If there is any fault in E-meter the LED will glow. EEPROM (Electrically Erasable Programmable Read Only Memory) used as flash memory to store a data. The proposed system neglects the regular digital meter reading system and allows remotely access the electronic meter. Legitimate validation, user can get to the created webpage points of interest from anyplace on the planet. The advantages of this project are to reduce cost and save more power and also reduce man power and time consumption. This project is implemented is hardware and software used are ARUDINO IDE (using embedded C language).Â Â